The Use of Artificial Intelligence for Improving Traffic Management in Intermatic - Gorta, Tadej; Živković, Sašo; Vukovič, Goran (Prometna varnost v lokalnem okolju: problemsko-učno sodelovanje z Intermatic d.o.o., 2026)
This research focused on the possibilities of using artificial intelligence in traffic management. The topic of the research originates from everyday situations in which users frequently encounter traffic congestion, traffic restrictions, and systems that, in their opinion, are not always fully adapted to actual road conditions. The aim of the research was to determine whether artificial intelligence could represent meaningful support in traffic management and in which areas its use could be most beneficial. To obtain data, a survey was conducted among traffic infrastructure users, and expert opinion from the field of traffic planning was obtained. Descriptive statistics and interpretation of collected responses were used for the analysis. The results showed that participants frequently perceive issues related to traffic flow and traffic restrictions, while generally expressing a positive attitude toward intelligent traffic systems. Particularly strong support was observed for adaptive traffic light management. The main concern raised by participants was the possibility of system errors and system reliability. Based on the research, it can be concluded that artificial intelligence represents an interesting opportunity for the further development of traffic systems, especially as support for monitoring, adaptation, and prediction of traffic conditions.